The combustion of solid paraffin wax and of liquid glycerol in a fluidised bed. (1st July 2017) - Menon, A.; Waller, N.; Hu, Wenting; Hayhurst, A.N.; Davidson, J.F.; Scott, S.A.
Highlights: In a hot bed of alumina sand, fluidised by air, paraffin wax burns like a plastic. When wax is fed on top of a bed, at least half its carbon-content ends up as soot. If wax is fed low down such a bed, no soot is produced – only CO or CO2. If glycerol enters low down a bed, it burns to CO or CO2, without soot appearing. Bubbles of fuel and air burn in a bed >800 °C, but explode above a cooler bed. Abstract: Two fuels were burned in electrically heated beds of alumina sand, fluidised by air. The fuels were: (i) paraffin wax, which is a solid containing 100% volatile matter and (ii) glycerol, a liquid, whose potential as a fuel needs assessing. The bubbling fluidised beds were held in the range 400–900 °C. Pieces of paraffin wax burned like a plastic, so when fed on top of a bed, the wax floated and generated clouds of soot. Soon, it then sank into the bed. When the sand was below ∼800 °C, combustion occurred noisily in exploding bubbles leaving the bed. In beds hotter than ∼800 °C, combustion proceeded in bubbles fairly low in the bed and was controlled by the mixing of hydrocarbon vapours (from the wax) with the fluidising air. If wax were fed half way up a bed, bubbles of hydrocarbon vapours were quickly produced; they ascended and mixed with the fluidising air. In a bed below 800 °C, combustion mainly occurred noisily in bubbles just after leaving the bed, but in a hotter bed, there was quieter burning in smaller bubbles, before they reached the top of the bed. Glycerol behaved similarly, when fed into the middle of a bed. Thus bubbles of glycerol vapour were formed; they mixed with air ascending the bed as either bubbles or percolating between particles. Again bubbles exploded noisily at the top of a bed below 800 °C. With the bed above 800 °C, glycerol burned inside smaller bubbles below the bed's upper surface. No soot was observed when burning glycerol in such a hot bed, yielding CO and CO2 as the only products of combustion. It appears that burning glycerol cleanly in a hot fluidised bed is a feasible proposition.